2015
DOI: 10.1038/nature15248
|View full text |Cite
|
Sign up to set email alerts
|

Erosion of the chronic myeloid leukaemia stem cell pool by PPARγ agonists

Abstract: Whether cancer is maintained by a small number of stem cells or is composed of proliferating cells with approximate phenotypic equivalency is a central question in cancer biology. In the stem cell hypothesis, relapse after treatment may occur by failure to eradicate cancer stem cells. Chronic myeloid leukaemia (CML) is quintessential to this hypothesis. CML is a myeloproliferative disorder that results from dysregulated tyrosine kinase activity of the fusion oncoprotein BCR-ABL. During the chronic phase, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(234 citation statements)
references
References 34 publications
12
216
1
Order By: Relevance
“…33,34 However, the LSC population is heterogeneous, consisting of a mixture of leukemic cells with differences in TKI sensitivity as well as residual healthy stem cells and progenitors. 10,31,35 Single-cell gene expression analysis offers the possibility to identify distinct subpopulations within the stem cell population in CML while directly discriminating between leukemic and normal cells based on BCR-ABL expression.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 However, the LSC population is heterogeneous, consisting of a mixture of leukemic cells with differences in TKI sensitivity as well as residual healthy stem cells and progenitors. 10,31,35 Single-cell gene expression analysis offers the possibility to identify distinct subpopulations within the stem cell population in CML while directly discriminating between leukemic and normal cells based on BCR-ABL expression.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Several recent studies have reported that targeting PPARγ might be an effective adjunct therapy in leukemia. In a very recent study, Prost et al 25 demonstrated that PPARγ agonists synergistically reduced the number of colony-forming cells in patients with chronic myeloid leukemia (CML). Lin et al 26 showed that the expression levels of ABC transporters and PTEN in tumor cells are important determinants of combination therapy efficacy and proposed that PTEN status of the tumor should be taken into account during the analysis of the clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown if leukemia cell growth is dependent on glucose metabolism activated by suppressing FBP1, and if inhibition of FBP1 impairs mitochondria metabolism in leukemia. PPARγ agonist glitazones decreases expression of STAT5 target genes, HIF2α and CITED2 , and disrupts quiescence and stemness of chronic myeloid leukaemia (CML) stem cells LSCs [63]. Further studies are needed to determine if PPARγ activation impairs glucose metabolism by increasing FBP1 expression in CML LSCs.…”
Section: Antagonizing Pparγ Signaling Expands Human Hscsmentioning
confidence: 99%